Effective risk based supervision: responding to the crisis - Bauer, Helmut (Henry Stewart Talks, 2009)
The crisis, Implications for risk based supervision, Historical perspective on the development of risk-based supervision and regulation, Better regulation and regulatory dialectic as the key drivers, Pending regulatory responses to the crisis, A policy-mix of micro and macro-prudential supervision as the new supervisory paradigm
Updated at 2009/09/29